Optimality, cost minimization and the design of arterial networks - Alun D. Hughes (Artery Research, 2015)
The arterial circulation acts as a network to deliver nutrients and oxygen to cells. The design of the cardiovascular system is subject to a variety of constraints and costs. It has been postulated that the design of the arterial network might be understood in terms of the need to minimize competing ‘costs’ within the context of physical or material limits to the system. These designs can also be envisaged as being subservient to space filling or fractal considerations. The signalling mechanisms underlying these designs remain to be fully characterized although shear stress, wall tensile stress and metabolic stimuli are likely candidates. I will also review evidence that deviations from a minimal cost condition or optimal design may provide both a measure of disease severity and insights into the underlying disease mechanism.